Electrohydrodynamically Printed High‐Resolution Full‐Color Hybrid Perovskites. (4th July 2019) - Zhu, Menghua; Duan, Yongqing; Liu, Nian; Li, Hegeng; Li, Jinghui; Du, Peipei; Tan, Zhifang; Niu, Guangda; Gao, Liang; Huang, YongAn; Yin, Zhouping; Tang, Jiang
Abstract: Hybrid perovskites show enormous potential for display due to their tunable emission, high color purity, strong photoluminescence and electroluminescence. For display applications, full‐color and high‐resolution patterning is compulsory, however, current perovskite processing such as spin‐coating fails to meet these requirements. Here, electrohydrodynamic (EHD) printing, with the unique advantages of high‐resolution patterning and large scalability, is introduced to fabricate full‐color perovskite patterns. Perovskite inks via simple precursor mixing are prepared to in situ crystallize tunable‐ and bright‐photoluminescence perovskite arrays without adding antisolvent. Through optimizing the EHD printing process, a high‐resolution dot matrix of 5 µm is achieved. The as‐printed patterns and pictures show full color and high controllability in micrometer dimension, indicating that the EHD printing is a competitive technique for future halide perovskite‐based high‐quality display. Abstract : Electrohydrodynamic (EHD) printing with the unique advantages of high‐resolution patterning and large scalability is introduced to fabricate full‐color perovskite patterns. Perovskite inks via simple precursor mixing are prepared to in situ crystallize tunable‐ and bright‐photoluminescence perovskite arrays without adding antisolvent. Through optimizing the EHD printing process, a high‐resolution dot matrix of 5 µm is achieved.